Preventive Measure and Action towards Livestock disease: Law on Animal Husbandry and Animal Health - Budiman, Haris; Yuhandra, Erga; Faisal, Koko Ahmad (Universitas Kuningan, 2024)
The research aims to examine the implementation of Law Number 18 of 2009: Animal Husbandry and Animal Health, the preventive measure, and its action. The urgency of the research is to raise people's awareness of the importance of livestock health and to effectively enforce existing regulation. Thus, the potential impact on human health and the livestock economy could be mitigated. Meanwhile, to collect data, analyse difficulties, and find solutions, the researchers employed empirical-juridical approaches such as surveys, interviews with relevant parties, and field observations in Kuningan Regency. The findings revealed that the Animal Husbandry and Animal Health Law explicitly regulates preventative and remedial measures for livestock diseases, highlighting the role of both national and local governments in advancing animal health. In addition, the government regulation on veterinary authorities’ states all of the topics, including preventive action, livestock traffic, infrastructure, and facilities. The execution of the so-called policies at the regional level reveals a multitude of interrelated barriers. The inability to implement policies can be attributed to a number of factors, including inconsistent regulations between regional and higher levels of legislation, a lack of qualified human resources, inadequate facilities and infrastructure, the effect of local customs and culture, and the quality of community education. To sum up, the investigation has improved our comprehension of the effectiveness of the laws. Yet, to improve the livestock’s health and wellbeing and minimise its disease transmission, it is advised to enhance compliance and best practices related to livestock management.